The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3892/etm.2022.11151
|View full text |Cite
|
Sign up to set email alerts
|

Butorphanol reduces the neuronal inflammatory response and apoptosis via inhibition of p38/JNK/ATF2/p53 signaling

Abstract: Neuronal cell apoptosis is a complex pathophysiological change that occurs following spinal cord injury (SCI) and affects self-repair. Therefore, preventing neuronal cell apoptosis can promote the recovery of nerve function. The present study aimed to investigate the effects of butorphanol on neuronal inflammatory response and apoptosis. The effects of butorphanol on cell viability and pathway-related protein expression were first assessed using the CCK8 and western blot assays, respectively. Lipopolysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…( ## p < 0.01 or # p < 0.05). The results were in accordance with these previous reports that butorphanol reduced brain and neurological damage and relieved the expression of in ammatory cytokines 12,19 . Arterial blood gas analysis was also one of the important criteria to assess the gas exchange extent and destruction of the alveolar wall 20,21 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…( ## p < 0.01 or # p < 0.05). The results were in accordance with these previous reports that butorphanol reduced brain and neurological damage and relieved the expression of in ammatory cytokines 12,19 . Arterial blood gas analysis was also one of the important criteria to assess the gas exchange extent and destruction of the alveolar wall 20,21 .…”
Section: Discussionsupporting
confidence: 93%
“…Butorphanol is widely used in the clinic as a lipid-soluble anesthetic drug with e cient analgesic effects 12,16,17 . In recent years, a series of reports have shown that butorphanol decreases the levels of proin ammatory cytokines or increases the levels of antiin ammatory cytokines to reduce organ injury and cell apoptosis [11][12][13]18 . However, the underlying anti-in ammatory mechanism of butorphanol has not been fully demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…on the whole, these results suggested that S100a1 expression was upregulated in the Pc12 cell model of LPS-induced inflammation. Subsequently, 5 µg/ml lPS was used for Pc12 cell model establishment to explore the biological function of S00a1 in lPS induced Sci model in vitro as the reported studies (30)(31)(32).…”
Section: S100a1 Expression Is Upregulated In the Pc12 Cell Model Of L...mentioning
confidence: 99%